Effect of Macroeconomic Factors on The Small-Medium Enterprises Loans - Adhisty Mohammad Khariza; Arintoko Arintoko; Suprapto Suprapto (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2020)
Small-medium enterprises (SMEs) are the main pillar of the Indonesian economy. Based on 2016’s Economic Census, most businesses in Indonesia are SMEs, while SMEs absorb the majority of the workforce. The empowerment of SMEs is one way to improve the economy. To empower the SMEs sector, the Indonesian government launched the Kredit Usaha Rakyat (KUR) since 2007. The lasts policy is the provision of the mild interest rate for KUR since 2016. The hope is that with a mild interest rate, SMEs can get affordable financing access so they can be the driving force of the economy. However, credit demand is not only influenced by interest rate but other macroeconomic factors such as Gross Domestic Product and inflation. Also, this study will look at how development disparities between the West Indonesia Region and East Indonesia Region affect credit demand. This research is intended to see the effect of macroeconomic factors on Small-medium enterprises loans. Source of data is taken from Indonesia Badan Pusat Statistik. Panel data use 2011-2018 time-series data and 33 provinces cross-section data are used to investigate the relationship of SMEs’ Loans with these macroeconomic factors. The result show that Interest Rate, GRDP, and Inflation, effect on SMEs Loans in a respectively different manner. However, the development disparities between West Indonesia Region and East Indonesia Region has no significant effect on SMEs’ loans. The study concludes that macroeconomic activities are important indicators not only the interest rate. So, the government should not only focus on interest rate policy but also other macroeconomic factors. Keyword: Macroeconomic Factors, SMEs’ Loan, Kredit Usaha Rakyat (KUR), Panel Data